2018
DOI: 10.1109/tia.2017.2768535
|View full text |Cite
|
Sign up to set email alerts
|

An Efficiency-Optimal Control Method for Mono-Inverter Dual-PMSM Systems

Abstract: Current research and development programs in aviation are promoting new technological advances to make electrical systems cheaper, lighter and more reliable. Mono-Inverter Dual-Permanent Magnet Synchronous Motor (MIDPMSM) systems tend to share the static converters in electro-mechanical systems by connecting motors in parallel.However several studies have shown that the efficiency of this configuration is lower than those with a traditional Mono-Inverter Mono-PMSM configuration, especially when unequal load to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The output function is defined as the speed of the two machines to achieve speed tracking control. θ d must be used to manipulate the system efficiency [14]. The state variables θ 1 and θ 2 are changed to θ d so that the number of states is reduced.…”
Section: Lti Model Of a Midpmsm System A State-space Model Of A mentioning
confidence: 99%
See 2 more Smart Citations
“…The output function is defined as the speed of the two machines to achieve speed tracking control. θ d must be used to manipulate the system efficiency [14]. The state variables θ 1 and θ 2 are changed to θ d so that the number of states is reduced.…”
Section: Lti Model Of a Midpmsm System A State-space Model Of A mentioning
confidence: 99%
“…The controller structure of a MIDPMSM system must be designed respect to the system constraints [14]. Among the unconstrained variable, θ d must be selected as constrained variable and used to regulate the efficiency of the system.…”
Section: B Order Reducing Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Using both SMC and deadbeat-based PCC the author is able to achieve robustness in current and speed tracking. The work of Liu and Fadel [45] gives Mono-Inverter Dual-PMSM system to share the static converters in electro-mechanical connected in parallel. This model provides both feasibility and performance improvement.…”
Section: Review Of Existing Resourcesmentioning
confidence: 99%
“…Reducing the number of switching devices is desirable; therefore, many research results have shown simplified configurations for DMDS. For example, a reduced-switch-count inverter [1][2][3], a nine-switch inverter [4][5][6][7], a mono inverter [8][9][10], a five-leg inverter [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], and so on.…”
Section: Introductionmentioning
confidence: 99%